THE MOORE-PENROSE INVERSE OF TRIDIAGONAL SKEW-SYMMETRIC MATRICES. II - Hakopian, Yuri R.; Manukyan, Avetik H.; Mikaelyan, Hamlet V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
This article is the second part of the work started in the previous publication by the authors [1]. The results presented here relate to deriving closed form expressions for the elements of the Moore-Penrose inverse of tridiagonal real skew-symmetric matrices of odd order. On the base of the formulas obtained, an algorithm that is optimal in terms of the amount of computational efforts is constructed.
Keywords: Moore-Penrose inverse; skew-symmetric matrix; tridiagonal matrix